Formative, Restorative and Transformative Learning: Insights into the Critical Consciousness of Social Activists - Donna M. Chovanec; Elizabeth A. Lange (Adult Education Research Conference, 2007)
Based on our research with diverse social activists in North and South America, we explore the central importance of critical consciousness and how it develops. We analyze the formation, restoration and transformation of critical consciousness in social activists and discuss implications for adult education.